Looking Beyond the Climate Change Convention to Attain Global Sustainability Targets - Murari, Kalpana S (European Journal of Sustainable Development, 2016)
Sustainable Development (SD) is evolving into a major discourse of international law. Very few nations have incorporated the principle within their domestic laws. It is time SD is taken up legally as an aspect of the regulatory domain and implemented globally and nationally. Arctic is one of region that can aid in managing global temperatures if monitored and verified under a mandatory ‘monitoring, reporting and verification’ (MRV) system. The role of extractive industries that involves gas flaring and increasing shipping activity in the region can lead to increase in Black Carbon (BC) emissions that are considered climate related pollutant. The Arctic is governed by a collection of legally non-binding soft-law multilateral and bilateral agreements and by the United Nations Convention on Law of the Sea (UNCLOS). It is overseen by the Arctic Council, a voluntary group consisting of nations that border the Arctic Ocean with goals of sustainable development and protection of the Arctic environment. The effect of BC has been thoroughly and scientifically examined and reports are indeed damning. BC emissions have a direct influence on the sea level rise, a fall out of climate change that is threatening not just a group of people but group of nations that are weak to raise their voice against powerful developed nations. It is time for a binding regulatory and legal regime to curb BC emissions to prevent future sea level rise. Is the collective conscience of the international community waking up to the crucial role of Arctic in tackling climate change impacts? Can we step up our efforts to actually protect the planet? Can we look beyond the Climate Change Convention for some serious answers? Are we there yet? Yes, IMO just published an investigative report on BC emissions. Key Words: Arctic Black Carbon, (BC) Verification of Emissions Reduction, MRV, Effects Doctrine, Global Sustainability Targets, Shipping Emissions